2019
DOI: 10.1186/s12950-019-0224-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional abnormalities of penile cavernous endothelial cells result in erectile dysfunction at experimental autoimmune prostatitis rat

Abstract: Background There is growing recognition of the association of CP/CPPS accompany with ED. However, the specific mechanism of action remains unclear. The aim of this study was to investigate structural and functional abnormalities of cavernous endothelial cells in EAP rat, which may result in the ED. Methods we use rat prostate protein extract supplemented with immunoadjuvant to induce EAP rat, ICP and MAP were measured and inflammatory factor infiltration, Akt, eNOS, AR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…In this study, we used EAP rats as subjects to explore the mechanism on the high incidence of PE in patients with prostatitis. Previous studies have shown that EAP rat is a mature animal model mimicking human CP/CPPS 8‐11,23 . However, no studies have been conducted to observe and evaluate the ejaculatory behavior of the EAP model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used EAP rats as subjects to explore the mechanism on the high incidence of PE in patients with prostatitis. Previous studies have shown that EAP rat is a mature animal model mimicking human CP/CPPS 8‐11,23 . However, no studies have been conducted to observe and evaluate the ejaculatory behavior of the EAP model.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, EAP model establishment followed the same procedure previously reported by other scholars 8,23 . The PPE concentration was quantified and adjusted to 20 mg/mL by spectrophotometry.…”
Section: Methodsmentioning
confidence: 98%
“…The study was conducted in line with the "Guidelines for the Care and Use of Laboratory Animals" published by the National Institutes of Health and approved by the Animal Science Committee of Tongji University. EAP rats was established as previously reported [11,12]. Ten rats were used for preparing autologous prostate tissue homogenate supernatant (PTHS).…”
Section: Establishment Of Eap Rat Modelmentioning
confidence: 99%
“…Rats was sacrificed at 45th day after the first immunization. At 45th day after the first immunization, the max intracavernous pressure (ICP) and the ratio of max ICP to mean systemic arterial pressure (max ICP/ MAP) were determined to assess the erectile function as previously reported [11,12]. The erectile response was elicited by electrical stimulation on the cavernous nerve and quantified by calculating the max ICP/MAP.…”
Section: Assessment Of Erectile Functionmentioning
confidence: 99%
See 1 more Smart Citation